Maritime Language Services for Shanghai International Shipping Center: An Innovative Model and Its Implementations - Liu, Yang (Journal of Language Service Studies, 2026)
The construction of Shanghai’s International Shipping Center has entered into a more advanced phase of development, in which the soft infrastructure such as language service capabilities manifested its indispensable role. Yet the potential of maritime language services in the pursuit of the Center’s capacity to sustain global competitiveness has been underestimated. The current provision of maritime language services is frequently regarded as a peripheral supporting function rather than a strategically valuable asset managed in a systematic and standardized manner. To address this gap, this study employs a design-oriented research approach. It introduces an innovative tripartite collaborative governance model that integrates Government, Industry, and Academia. The model is structured around four interconnected strategic pillars—strategic positioning, industrial integration, talent cultivation, and technological empowerment. Through this framework, the paper identifies and elaborates on six key growth areas, such as building integrated service platforms and cultivating interdisciplinary talent, which translate the model into actionable implementation pathways. This research makes a dual contribution. Conceptually, it advances the field by re-framing maritime language services from a discrete operational concern into a strategically managed component of soft infrastructure, providing a novel governance lens. Practically, it offers a systematic blueprint for policymakers and industry stakeholders. The proposed model and its identified growth areas directly contribute a feasible roadmap for enhancing the language service ecosystem, thereby injecting new vitality and a substantive stimulus into the high-quality, competitive development of Shanghai's International Shipping Center.